Mechanism of pyroptosis in neurodegenerative diseases and its therapeutic potential by traditional Chinese medicine - Liao, Yanfang; Wang, Xue; Huang, Liting; Qian, Hu; Liu, Wei (Frontiers in Pharmacology, 2023)
Neurodegenerative diseases (NDs) are disorders characterized by degenerative degeneration of neurons and loss of their function. NDs have a complicated pathophysiology, of which neuroinflammation and neuronal death are significant factors. The inflammatory process known as pyroptosis ("fiery death") is caused by a family of pore-forming proteins called Gasdermins (GSDMs), which appears downstream from the activation of the inflammasome. Clear evidence of enhanced pyroptosis-related proteins activity in common NDs has coincided with abnormal aggregation of pathological proteins (such as Aβ, tau, α-synuclein et al.), making pyroptosis an attractive direction for the recent study of NDs. The purpose of this review is to provide an overview of the molecular mechanisms driving pyroptosis, the mechanistic links between pyroptosis and NDs, and emerging therapeutic strategies in Traditional Chinese Medicine (TCM) to inhibit pyroptosis for the treatment of NDs.